CP-137 Impact of the pharmacist in the optimisation of antiretroviral treatment in HIV patient consultations. (24th March 2015) - Escudero, B; Diez, A; Martín, A; Alonso, V; Sánchez, A
Abstract : Background: HIV is an expensive disease. Therefore, multidisciplinary collaboration is essential to improve treatment efficiency. Purpose: To evaluate the impact of the integration of a pharmacist in HIV consultations to optimise antiretroviral treatment (ART). Material and methods: Quasi-experimental prospective study in HIV patients with ART in a university hospital. The resident pharmacist was integrated in the HIV specialist consultations for one month (October 2013). Viral load (VL), CD4, duration and treatment lines, resistances and comorbidities were evaluated. The pharmacist reviewed the ART and possible switches to optimise it in order to reach the pharmacoeconomic indicator set by the Health System in 2013 (683 euros/month per patient). Costs were assessed using ex-factory prices. Results: 70 patients (75% male) were included, mean age 47 (range 28–73) years old. 9 patients had detectable VL (VL ≥ 50 copies/ml): 4 non-adherent (adherence < 90%), 2 treatment-naive patients, 2 blips and 1 resistant to ART. Mean CD4 cell count was 583 (49–1.484)/mm 3 . Regarding ART, 5 patients were on monotherapy, 4 dual therapy, 59 triple therapy and 2 with four drugs. Monthly drug costs per patient were between 358 and 1, 483 euros. 40% (28 patients) did not reach the pharmacoeconomic indicator goal. Of them, after the pharmacist's intervention, in 18% (5 patients) one ART drug was modified or suspended and in 32% (9 patients), although the interventions were accepted, the ART changes depended on the next blood test. In the other 50% (14 patients), a change was not appropriate: 6 low adherence, 2 on treatment less than 6 months, 2 psychiatric conditions, 2 resistant patients and 2 HBV co-infections. The drug savings due to the pharmacist's interventions were 14, 615 euros/year in our hospital. Conclusion: The inclusion of the pharmacist for a month, extrapolated to the total of patients on ART in our hospital (661 patients), would yield annual drug savings of €138, 005. Therefore, pharmacist integration into the medical team improves ART efficiency. References and/or Acknowledgements: No conflict of interest.